2 - Governance Issues and the Covid-19 Pandemic in West Africa: Are There Any Linkages? - Félix Fofana N'Zue,; Adjoua Math Komenan, (Africa Development, 2023)
This article contributes to a better understanding of the possible interaction between the spread of the Covid-19 pandemic in the ECOWAS countries and the state of governance. More specifically, it determines the relationship between governance and the number of Covid-19 confirmed cases by the end of September 2021, the relationship between tourist arrivals and external debt and the number of confirmed cases. The data was collected over 2020 and 2021. Correlation and multiple regression analysis were used to assess the strength of association between the variables and possible causation respectively. The study found positive and significant correlation between all the governance variables, except for political stability. There was a strong association between tourist arrivals, external debt, and infection rates. Governance did not significantly impact the infection rate, whereas the number of tourists and per capita external debt did so significantly. It is therefore recommended that more stringent actions be taken to reinforce safety measures at all entry points in the ECOWAS region and that development partners look closely at the reliability of the numbers of confirmed cases to ensure th t the data collected is not manipulated simply to attract foreign resources.